Cenerella: Psicofavola femminista. A cura di Marco Calogero Battaglia - Mangiacapre, Lina (Mimesis Journal, 2021)
Cenerella is the first play written and directed by Lina Mangiacapre. Staged in 1973 in Naples, it represents the first step in her career as multifarious artist and feminist activist. Lina Mangiacapre re-wrote Cinderella’s story from a feminist perspective and staged it in collaboration with the feminist group (Le Nemesiache) that she founded in 1970. The idea of rethinking classical texts and myths from a femminist standpoint will be pivotal in her plays as well as in her movies and in her novels. This play was intended to participate in the debate around the Italian family that took place in Italy during the Seventies. She challenged the Italian family as an institution and suggested that a change was both possible and needed. In her play Cinederella became a more complex and modern figure, struggling to gain agency in a world ruled by men.